PENERAPAN SIMULASI USAHA BERBASIS PROJECT-BASED LEARNING UNTUK MENINGKATKAN KOMPETENSI KEWIRAUSAHAAN SISWA AKUNTANSI DI SMK PERBANKAN RIAU - Yessa Meiresa; Andri Eko Prabowo (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
The low level of entrepreneurial competence among accounting students-particularly regarding business planning, creativity, business management, and financial statement preparation-highlights the need for more innovative learning models. One viable alternative is a business simulation based on Project-Based Learning (PjBL), as it offers students authentic learning experiences. This study aimed to enhance the entrepreneurial competence of accounting students at SMK Perbankan Riau through the implementation of a PjBL-based business simulation. The study employed the Classroom Action Research (CAR) method following the Kemmis and McTaggart model, comprising the stages of planning, action, observation, and reflection. The participants consisted of 32 students from the Class XI Accounting 2 program. Data were collected through observation, project assessments, and documentation, and subsequently analyzed using both quantitative and qualitative descriptive methods. The results indicate that the PjBL-based business simulation increased student learning engagement from 77.5% to 84% and yielded an average project score of 82, with a class mastery rate of 81.25%. Thus, this model is effective in enhancing the entrepreneurial competence of accounting students.